Antibiofilm and antibacterial properties of Streptococcus and Staphylococcus from the oral microbiome - Dawis, Nurul Hasanah; Mohd Nazli, Muhammad Danish; Azhan, Nik Airin Syazlin; Aazmi, Mohd Shafiq; Abd Aziz, Aziyah; Abdullah, Mohammad Faiz Foong (Faculty of Applied Sciences, 2025)
The human oral microbiome plays an important role in balancing beneficial and harmful microorganisms in the oral cavity. Certain oral bacteria are known to produce substances that inhibit the formation of microbial biofilm and growth of potentially pathogenic microorganisms. The oral microbiome of the Malaysian population is largely uncharacterized, and there is very little information on its diversity and potential as a source of probiotics or antibiofilm and antibacterial metabolites. The objectives of this study are to characterize the taxonomic composition of the oral microbiome in selected healthy Malaysian subjects; and to assess the capacity of bacterial isolates from oral microbiome to produce antibiofilm and antibacterial compounds. Metagenomic sequencing showed that the oral microbiome includes predominantly bacteria from the phyla Firmicutes, Bacteroidetes, Proteobacteria, Fusobacteria and Actinobacteria while Streptococcus, Haemophilus, Neisseria, Phorphyromonas and Fusobacterium are the most represented genera Altogether, 117 bacterial cultures were successfully isolated from these microbiomes, where 14 (12.0%) isolates inhibited Staphylococcus epidermidis (ATCC 35984) biofilm formation at maturation stage with highest activity observed at 94.8%. Twelve (10.3%) isolates displayed antibacterial activity with the highest activity observed against Streptococcus mutans (ATCC 25175) at 76.9%, followed by Bacillus subtilis (ATCC6633) at 56.6%; but no activities were observed against E. coli (ATCC 25922) or S. aureus (ATCC 25923). Identification via 16S rRNA sequencing showed that the majority of the oral bacterial isolates displaying the antibiofilm and/or antibacterial activities were Streptococcus salivarius followed by strains of S. aureus. Two of these isolates, SA78 and SA10, produced both antibiofilm and antibacterial activities and were identified to be S. salivarus suggesting the potential of this species in treating oral infections and improving dental health. Understanding the oral microbiome composition and using resident beneficial bacterial species as oral probiotics may provide a novel strategy for addressing oral diseases.